Answers

2016-01-04T23:24:43+08:00
Consider that M is the initial point and N is the final point.
The formula of the distance in two coordinate system from M to N is
 d_M_N = \sqrt{(x_N - x_M)^2+(y_N - y_M)^2}
With x_N = 7, x_M = -3, y_N = -3, y_M=1,
d_M_N= \sqrt{[7-(-3)]^2+(-3-1)^2}= \sqrt{10^2+(-4)^2}=10.77

0
  • Brainly User
2016-01-05T16:49:52+08:00
Distance between two points M and N:

D _{MN} =  \sqrt{(x _{2}- x_{1}) ^{2}+(y _{2}-y _{1} )^{2}     }

Where:
M = (x₁, y₁) = (-3, 1) 
N = (x₂, y₂) = (7, -3)

x₁ = -3      x₂ = 7
y₁ = 1       y₂ = -3

D _{MN} =  \sqrt{(7 - (-3) ^{2}+(-3 - 1) ^{2}  }

D _{MN} =  \sqrt{(10) ^{2}+(-4) ^{2}  }

D _{MN} =  \sqrt{100 + 16}  =   \sqrt{116}

D _{MN} =  \sqrt{(4)(29)} 2 \sqrt{29}

D _{MN}  ≈ 10.77



0